Behaviour change interventions to increase physical activity in hospitalised patients: a systematic review, meta-analysis and meta-regression. (24th July 2021) - Taylor, Nicholas F; Harding, Katherine E; Dennett, Amy M; Febrey, Samantha; Warmoth, Krystal; Hall, Abi J; Prendergast, Luke A; Goodwin, Victoria A
Abstract: Background: Low physical activity levels are a major problem for people in hospital and are associated with adverse outcomes. Objective: This systematic review, meta-analysis and meta-regression aimed to determine the effect of behaviour change interventions on physical activity levels in hospitalised patients. Methods: Randomised controlled trials of behaviour change interventions to increase physical activity in hospitalised patients were selected from a database search, supplemented by reference list checking and citation tracking. Data were synthesised with random-effects meta-analyses and meta-regression analyses, applying Grades of Recommendation, Assessment, Development and Evaluation criteria. The primary outcome was objectively measured physical activity. Secondary measures were patient-related outcomes (e.g. mobility), service level outcomes (e.g. length of stay), adverse events and patient satisfaction. Results: Twenty randomised controlled trials of behaviour change interventions involving 2, 568 participants (weighted mean age 67 years) included six trials with a high risk of bias. There was moderate-certainty evidence that behaviour change interventions increased physical activity levels (SMD 0.34, 95% CI 0.14–0.55). Findings in relation to mobility and length of stay were inconclusive. Adverse events were poorly reported. Meta-regression found behaviour change techniques of goal setting (SMD 0.29, 95% CI 0.05–0.53) and feedback (excluding high risk of bias trials) (SMD 0.35, 95% CI 0.11–0.60) were independently associated with increased physical activity. Conclusions: Targeted behaviour change interventions were associated with increases in physical activity in hospitalised patients. The trials in this review were inconclusive in relation to the patient-related or health service benefits of increasing physical activity in hospital.